Analysis of El Ni˜no Impact and the Price of Food Commodities on Inflation - Bronson Marpaung; Hermanto Siregar; Lukytawati Anggraeni (Jurnal Ekonomi Indonesia, 2019)
Volatile foods are a concern because this group is a significant contributor to inflation. Food production is very vulnerable to supply disruptions such as El Ni˜no weather and other weather disturbances. This study analyzes the influence of El Ni˜no on food Commodities and, inflation, in 25 provinces in Indonesia in 2008–2015 using the data panel method. The dependent variable in this study is inflation. While the independent variables are food commodities such as Prices of Chili, Onions, Rice, Soybeans, Corn, El Ni˜ no, and Inflation. El Ni˜no and the price of food commodities have a positive and significant effect on inflation.